(untitled) (International Journal of Engineering and Computer Science, 2016)
Digital Commerce is system of doing industry via computer networks. A man or woman sitting on his chair in front of a laptop/PC can access the entire services of the web to purchase or promote the products. In contrast to average commerce that’s implemented physically with effort of a individual to go & get products, ecommerce has made it easier for human to decrease physical work and to avoid wasting time. E-Commerce which was started in early 1990’s has taken a satisfactory jump in the world of computer systems, but the truth that has hindered the progress of e-commerce is protection. Protection is the task facing e-commerce at present & there is nonetheless various development made within the field of safety. The essential advantage of e-commerce over natural commerce is the user can browse on-line stores, compare prices and order merchandise sitting at home on their computer. In this paper to exposed different online market groups’ functionalities. Electronic Commerce is process of doing business through computer networks. A person sitting on his chair in front of a computer can access all the facilities of the Internet to buy or sell the products.